2014
DOI: 10.1016/j.shaw.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Workflow Interruptions and Failed Action Regulation in Surgery Personnel

Abstract: BackgroundWorkflow interruptions during surgery may cause a threat to patient's safety. Workflow interruptions were tested to predict failure in action regulation that in turn predicts near-accidents in surgery and related health care.MethodsOne-hundred-and-thirty-three theater nurses and physicians from eight Swiss hospitals participated in a cross-sectional questionnaire survey. The study participation rate was 43%.ResultsStructural equation modeling confirmed an indirect path from workflow interruptions thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Another approach lies in stochastic resonance whole body vibration that has been proven to reduce musculoskeletal complaints in different non-nursing occupations [61] , [80] , [81] . Elfering et al [21] examined whether or not a positive effect of such training can be found with OR nurses as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach lies in stochastic resonance whole body vibration that has been proven to reduce musculoskeletal complaints in different non-nursing occupations [61] , [80] , [81] . Elfering et al [21] examined whether or not a positive effect of such training can be found with OR nurses as well.…”
Section: Discussionmentioning
confidence: 99%
“…Another common stressor in healthcare is interruption at work [20] . According to Elfering et al [21] , interruptions at work may trigger failure in action regulation. Thus, interruptions during an OR nurse's work represent a threat to surgery outcomes and patient safety, and are stressful for OR nurses.…”
Section: Introductionmentioning
confidence: 99%
“…53 •2 retrospective observational studies were performed: they described interruptions reported by medical and paramedical staff. 59,60 •One interventional study tested a measure of interruption reduction in the OR. 61 Five phases of risk were defined during a surgical procedure (anesthesia induction, surgical briefing, specimen collection, final surgical counts and debriefing, anesthesia emergence).…”
Section: Studies' Methodologymentioning
confidence: 99%
“…Now, there are signi cant researches on interruptions in the process of health services delivery. Several attempts have been made to conduct observational studies that focus on a speci c department [15,16] or care provider and explore the frequency and effect of interruptions [3,17,18]. Moreover, some studies have just discussed a speci c source of interruption, such as a paging device [14,19], a communication device [20] or electronic medical record [21].…”
Section: Previous Studies Have Compared Work Ow Interruptions Among Different Medical Workplaces[8]mentioning
confidence: 99%